Musculoskeletal Factors and Geriatric Syndromes Related to the Absence of Musculoskeletal Degenerative Disease in Elderly People Aged over 70 Years. (18th November 2019) - Imagama, Shiro; Ando, Kei; Kobayashi, Kazuyoshi; Seki, Taisuke; Ishizuka, Shinya; Machino, Masaaki; Tanaka, Satoshi; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Nakashima, Hiroaki; et al.
Abstract : Purpose. To investigate factors with a significant relationship with the absence of musculoskeletal disease (MSD: osteoporosis, knee osteoarthritis (K-OA), and lumbar spondylosis (L-OA)) in elderly people ≥70 years old. Methods. The subjects were 279 people (134 males, 145 females, mean age: 75.2 years) who attended an annual health checkup and were prospectively included in the study. Osteoporosis was defined as %YAM ≤70%, K-OA as Kellgren–Lawrence grade ≥2, and L-OA as osteophytes of Nathan class ≥3. Subjects were divided into those with (group D) and without (group N) any MSD. Clinical variables including locomotive syndrome (LS), frailty, sarcopenia, and QOL (SF-36) were compared between the groups. Results . There was no significant difference in age or gender between group N (n = 54 ) and group D (n = 225 ). Lower BMI and pain, including neuropathic pain; greater back muscle strength, physical ability, and balance with eyes closed; larger lumbar lordosis, sacral inclination, and lumbar ROM; and smaller spinal inclination were found in group N. The rates of LS and sarcopenia were significantly lower and QOL was significantly higher in group N. Conclusions . This study firstly revealed the significant musculoskeletal factors and geriatric syndromes related to an absence of MSD, which may form the basis of interventions to improve QOL in elderly people ≥70 years old.